Interactive Learning Media Mission Task Powerpoint Based and Its Effectiveness on Student Learning Outcomes - Fadhilla, Nisvia Rima; Sulistyawati, Eka; Resti, Nalsa Cintya (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The online learning process and the use of instructional media which are still limited to printed books allow students to misunderstand mathematical concepts. This study aims to develop interactive learning media using power point and prove the quality of the media through the analysis of the validity, practicality and effectiveness of the media on student learning outcomes. The type of research used is Research and Development with the ADDIE development model includes Analysis, Design, Development, Implementation, Evaluate. The instruments used in this study were validation sheets, response questionnaires, and mathematics learning achievement test questions. The results of the validation of media and material experts obtained calculations of 269 and 247 with very valid categories. The results of the questionnaire validation obtained a score of 1,924 in the very practical category. The results of the study test after the application of learning media Mission Task obtained the percentage of classical completeness of 86.36%, this means that the media is effective on mathematics learning outcomes. if the students' comprehension results are included in the fairly high category on the indicator question number 3b and very high on the other question indicators based on the total scores of all students